2018
DOI: 10.1007/s10897-017-0209-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification as a Mutation Carrier and Effects on Life According to Experiences of Finnish Male BRCA1/2 Mutation Carriers

Abstract: Earlier studies have explored post-identification experiences of male BRCA1/2 mutation carriers, but more detailed knowledge of both their experiences and effects of identification as a carrier on their lives is required to improve genetic counseling. Thus, the aim of this study was to acquire deeper and broader insights into their experiences. Qualitative data were collected from theme-based interviews with 31 men carrying BRCA1/2 mutations in Finland, and analyzed using inductive content analysis. Three cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The target study population for the present study comprised cancer-free males and females; thus, a direct comparison with previous studies that targeted BRCA1/2 mutation carriers might be limited. Nonetheless, the associations of high income and non-disclosure of mutation-positive genetic test results with a change in attitude toward childbearing are comparable with those in previous studies [ 6 11 12 13 14 16 17 ]. Disclosure of BRCA1/2 mutation status was associated with higher levels of family support during decision-making [ 18 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The target study population for the present study comprised cancer-free males and females; thus, a direct comparison with previous studies that targeted BRCA1/2 mutation carriers might be limited. Nonetheless, the associations of high income and non-disclosure of mutation-positive genetic test results with a change in attitude toward childbearing are comparable with those in previous studies [ 6 11 12 13 14 16 17 ]. Disclosure of BRCA1/2 mutation status was associated with higher levels of family support during decision-making [ 18 ].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, BRCA1/2 mutation carriers’ partners are concerned about their children’s mutation status and risk of cancer. Female BRCA mutation carriers and their spouses are less likely to have children than non-carriers [ 4 5 6 ]. Carriers who do want to have children have the option of undergoing preimplantation genetic diagnosis (PGD), i.e., the process of selecting in vitro -fertilized embryos that are BRCA mutation-free before implanting them into the uterus [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the genetic test might have explained the strange occurrence of their rare disease, but it has also made it difficult to exonerate responsibilities for passing on the PV and triggered the fear that tumors might (re) appear, making them hyper-vigilant about their symptoms. Many of these positive (Bradbury et al, 2009;Kajula et al, 2018), neutral (Kajula et al, 2018), and especially negative (Hallowell et al, 2004;Kajula et al, 2018;Kenen et al, 2006;Underhill & Dickerson, 2011) approaches to knowing that one carries the PV were also described in previous qualitative studies about other hereditary cancers. In the present study, they were grounded in the context of four different types of experiences, reflecting the specificities of this hereditary condition.…”
Section: Discussionmentioning
confidence: 79%
“…Previous qualitative studies in other hereditary cancers have shown that genetic testing is contextualized within participants' broader experiences, and for some tumor-affected patients, it may fade in comparison with a cancer diagnosis (Shipman et al, 2017). Although neutral reactions can occur, some tumor-affected carriers have described strong emotional reactions and cancer worries when they received a positive genetic test result (Kajula et al, 2018). For some patients already affected with cancer, the burden of the genetic diagnosis has led to feelings of devastation, loneliness, sense of being different from others, worries about family reactions, or anxiety regarding the increased risk of developing a second cancer (Hallowell et al, 2004;Kenen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation